The judicial control of the sanctions imposed by the Commission in the field of competition law: the procedural flaws of the decisions (recent case law) - Moreno Molina, Angel M. (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
This essay explores the control (on procedural grounds) exercised by the European Union courts over the fines and other sanctions that the Commission may impose on the economic operators, in the framework of its powers and competences to enforce the articles 101 and 102 of the TFEU (anti-dumping and other illegal agreements and conducts). First, this contribution interprets the structure of legal rules applicable in this field, and further identifies the principles of procedure and the rights of companies in the framework of these procedures. Finally, the author presents a selection of some recent judgments handed down by the Luxembourg Courts in this field.